Ghana : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of accounting and auditing practices within the context of the Ghana institutional framework to ensure the quality of corporate financial reporting. The accounting and auditing practices in Ghana suffer from institutional weaknesses in regulation, compliance, and enforcement of standards and rules. Various weaknesses were identified in the laws and regulations governing financial reporting. Although Ghana Accounting and Auditing Standards have been based on International Accounting Standards and International Standards on Auditing, respectively, they are outdated and gaps exist in comparison with the international equivalents. Furthermore, national ethical requirements for auditors are not in line with international requirements. Full compliance with Ghana National Accounting Standards is not readily achieved; some listed companies inappropriately claim compliance with International Accounting Standards. There is inadequate adherence to auditing standards and professional ethics. Apart from the banking sector practice, monitoring and enforcement mechanisms are ineffective. These factors, as well as poor quality accounting education and training, have contributed to weaknesses of the financial reporting and auditing regime. The policy recommendations provided in this report focus on improving statutory framework, strengthening enforcement mechanisms, upgrading professional education and training, and enhancing capacity of regulatory and professional bodies.